Pemberdayaan Komunitas Lansia melalui Edukasi Kesehatan dan Pemeriksaan Dini Faktor Risiko Penyakit Kronis - Latipah, Siti; Sofiani, Yani; Rayasari, Fitrian; Siswandi, Iyar; Nugraha, Rizky; Jumaiyah, Wati; Aisyah, Aisyah; Nathasia, Dhea (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Diabetes mellitus (DM) is one of the major non-communicable diseases with a steadily increasing prevalence in Indonesia, including in island regions with limited access to healthcare services. This community service program was conducted on Lancang Island, Kepulauan Seribu. Objective: The purpose of this service was of improving elderly participants’ knowledge of diabetes management, conducting early detection through health screening, and providing education on healthy lifestyle practices. Method: The methods included interactive health education sessions and physical examinations covering random blood glucose, blood pressure, and cholesterol levels. Result: The results showed that the majority of the 101 elderly respondents exhibited significant chronic health risk factors. The average blood pressure was 152/88 mmHg, indicating a tendency toward hypertension. The mean random blood glucose level of 140 mg/dL suggested a predisposition to prediabetes and diabetes mellitus, while the mean cholesterol level reached 253 mg/dL, categorized as high. Conclusion These findings indicate that most elderly participants have not yet implemented optimal dietary management and physical activity, further exacerbated by limited health facilities and access in island areas. The educational intervention effectively increased participants awareness of disease risks and complications, as well as the importance of early detection. Overall, the promotive and preventive activities had a positive impact on improving knowledge, awareness, and motivation among elderly participants to adopt healthy lifestyles. This program is expected to serve as a foundation for sustainable community health development efforts in island regions.